Penguatan-parutan Terhadap Mod-mod Elektromagnet pada Pandu Gelombang Organik Tripalmitin - Mat Yunus, W. Mahmood (Universiti Putra Malaysia Press, 1997)
Grating-enhancement and characterization of electromagnetic modes in organic waveguides are presented. The intensity of P and S polarized light reflected from the gold grating with organic tripalmitin coating at varying twist angles was measured as a function of angle of incidence. The characteristic behaviour of TE and TM modes in terms of twist angles is discussed in detail. It was discovered that the maximum P-S conversion of TEl' TE2 and TM2 modes occurred at twist angles of 40, 50 and 64° respectively. In this experiment it was found that organic tripalmitin is a good candidate for waveguide material and needs to be studied in more detail.